Comparison of follicular T helper cells, monocytes, and T cells priming between newly diagnosed and rituximab-treated MS patients and healthy controls - Sheida Yahyazadeh; Nafiseh Esmaeil; Vahid Shaygannejad; Omid Mirmosayyeb (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: The use of anti-CD20 monoclonal antibodies like rituximab (RTX) to deplete B cells has practical therapeutic implications in multiple sclerosis (MS) patients. However, the therapy's impact on other immune cells is also important. Therefore, in this study, we assessed the effects of RTX therapy on Tfh cells, T cells, T cells priming, and monocytes in MS patients compared to newly-diagnosed MS patients and healthy subjects. Experimental approach: Thirty newly-diagnosed and RTX-treated MS patients and healthy control were included. Peripheral blood mononuclear cells were isolated from whole blood for assessment of Tfh cells, CD4+, CD8+, CD4+CD45RA+, CD3+HLA-DR+, and CD3+CD4+CD25+ T cells by flow cytometry. Whole blood was lysed by lysis solution to assess CD45+CD14+ monocytes by flow cytometry. Also, the serum level of interleukin 21 was measured by the ELISA method. Findings / Results: We showed that RTX treatment led to a decrease in Tfh cells and their predominant cytokine, interleukin 21. Also, we found a statistically significant reduction in CD3+HLA-DR+ and CD3+CD4+CD25+ T cells in RTX-treated patients compared to new cases and healthy control. Moreover, we found a decrease in the CD45+ CD14+ monocyte population in the RTX-treated group compared to the healthy control. Conclusion and implications: Our data suggest that following treatment with RTX, Tfh cells, monocytes, and T cells priming declined happened, and fewer T cells were activated. Also, due to the interaction between B cells and Tfh cells, Tfh targeting could be assessed as a therapeutic strategy in MS.